2015
DOI: 10.1038/nmeth.3685
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional force microscopy of cells in biopolymer networks

Abstract: We describe a technique for the quantitative measurement of cell-generated forces in highly nonlinear three-dimensional biopolymer networks that mimic the physiological situation of living cells. We computed forces of MDA-MB-231 breast carcinoma cells from the measured network deformations around the cells using a finite-element approach based on a constitutive equation that captures the complex mechanical properties of diverse biopolymers such as collagen gels, fibrin gels and Matrigel. Our measurements show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
344
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(372 citation statements)
references
References 39 publications
26
344
2
Order By: Relevance
“…Our results show that MDA-MB-231 cells exhibiting mesenchymal motility displace their surrounding collagen matrix much more extensively than previously reported for a mixed population of amoeboid and mesenchymal cells (Fig. S2B) (42). We note that fibroblasts exhibit even stronger strain-stiffening behavior than cancer cells of epithelial origin as reported in refs.…”
Section: From Cell To Ecm: Cells Exert Sufficient Strain To Locally Asupporting
confidence: 83%
“…Our results show that MDA-MB-231 cells exhibiting mesenchymal motility displace their surrounding collagen matrix much more extensively than previously reported for a mixed population of amoeboid and mesenchymal cells (Fig. S2B) (42). We note that fibroblasts exhibit even stronger strain-stiffening behavior than cancer cells of epithelial origin as reported in refs.…”
Section: From Cell To Ecm: Cells Exert Sufficient Strain To Locally Asupporting
confidence: 83%
“…The tangent elastic modulus between 3 and 7% axial strains (∼0.16 to ∼0.75 kPa) at 0.5, 1.0, and 2.0 mg/mL collagen concentrations is also shown from ref. 53. (D) Quantitative analysis of the melanoma cell invasion shows a biphasic response to the concentration of collagen.…”
Section: The Interplay Between Cell Contractility and Matrix Fiber Rementioning
confidence: 99%
“…More recently Steinwachs and colleagues have developed a physio-mimetic biopolymer based system that allows the direct quantification of the mechanical forces applied by cancer cells fully embedded within physiological relevant 3D network [63]. Another recent study has reported the use of stimulated emission depletion (STED) microscopy with TFM to solve one of the major shortcomings of this technique, the spatial resolution.…”
Section: Traction Force Microscopymentioning
confidence: 99%